Inovação, estudos CTS e comunicação científica: a divulgação das pesquisas de materiais cerâmicos e nanotecnologia - Resende, Letícia Passos (Universidade Federal de São Carlos, 2011)
The Centers for Research, Innovation and Diffusion (Cepid) of the Sao Paulo Research Foundation Centre are devoted to multidisciplinary basic research and innovation, knowledge transfer to business and public sectors, and interaction with the educational system. Hence the relevance of consistent public communication of science and technology. This masters dissertation carried out an analysis of the communication initiatives made by the Multidisciplinary Center for Development of Ceramic Materials (Sao Carlos, SP), a Cepid which became a National Institute of Materials Science and Nanotechnology. In the field of the science communication, the center output is vast and focuses on a research and development area in which increasing resources have been invested in Brazil. The center usually publishes online news releases and produced 68 programs of a TV series named From the classical ceramic to the nanotechnology , with 15 minute-length each, available in DVD and broadcasted on the University Channel of São Carlos. We studied such communication output with framing analysis. The results showed that aspects of great relevance to S&T communication were often absent from our sample, which indicates opportunities to advance the center performance in that field. We suggest the adoption of eight categories of information as news values in accordance with the context of the democratic model of science communication.
Keywords: Desenvolvimento social - ciência, tecnologia e sociedade; Comunicação pública; Nanotecnologia; Participação e comunicação; Comunicação científica; Informação; Cidadania; Estudos; Science communication; Information; Citizenship; STS Studies; Nanotechnology; CIENCIAS SOCIAIS APLICADAS